TUTURAN IMPERATIF DALAM NASKAH DRAMA OBLADI OBLADA TIGA NASKAH DRAMA TERPILIH KARYA DASRI AL-MUBARY - Wulan Ramadhani; Hermandra '; Elmustian ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: This research discusses about imperative speech in Obladi ObladaDrama Script Three Drama Script Selected by Dasri Al-Mubary. In general the problemstudied in this research about the form of imperative speech and meaning of imperativespeech in Obladi Oblada Drama Script Three Drama Script Selected by Dasri Al-Mubary. This research uses descriptive method with qualitative approach, data in theform of speech circuit. Technique used in this research that is technique of read andrecord. The source of this reseacrh from the Obladi Oblada Drama Script Three DramaScript Selected by Dasri Al-Mubary. The result of this study indicate there are 5 formsof imperative speech which amounted to 37 data, on the meaning there are 10 meaningao 17 meanings that exist in the Indonesian languange which amounted to 30 data.Overall data that writer earn amount 67 data. Imperative speech discusses theutterance between the speaker and the opponent of speech which has the meaning ofcommanding to the opponent said to do something in accordance with the desired bythe speaker. Imperative speech may contain statements in the form of a very harsh orcrude order with very subtle or polite requests.Key word : Imperative speech, Form and meaning, Obladi Oblada drama three drama scriptselected.